The Difference Compressive Strength of Scaffold Combination Chitosan and Aloe vera Extracted Water and Ethanol - Dwi Ayu Trisnawati; Sularsih; Widaningsih (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2019)
Background: Scaffold can be use in bone regeneration, but it should have similarities characteristic to a natural bone such as compressive strength that supported the process of growth and development of bone. This research use scaffold that made from chitosan and Aloe vera. Chitosan well-known as osteoconductive material, meanwhile Aloe vera was osteoinductive material. Purpose: The aim of this research was to compare compressive strength scaffold combinations of chitosan and Aloe vera extracted water and ethanol. Materials and Methods: Research design using post test only control group design with 36 scaffolds divided into 6 groups. Group 1 was scaffold Aloe vera extracted water (AVa), group 2 was scaffold Aloe vera extracted ethanol (AVe), group 3 was scaffold combination chitosan and Aloe vera extracted water 1: 1 (k-AVa1), group 4 was the scaffold combination of chitosan and Aloe vera extracted ethanol 1: 1 (k-AVe1), group 5 was scaffold combination of chitosan and Aloe vera extracted water 1: 2 (k-AVa2), and group 6 was scaffold combination of chitosan and Aloe vera ethanol extract 1: 2 (k -AVe2). Compressive strength test used Universal Testing Machine (Shimadzu Autograph–AGS–1kNX and using software Trapezium X). Data were analyzed using One Way ANOVA and Games Howell test. Results: The result of compressive strength AVa=1.36 MPa, AVe=1.03 MPa, k-AVa1=0.27 MPa, k-AVe1=0.11 MPa, k-AVa2=0.38 MPa, and k-AVe2=0.29 MPa. All groups have significant differences except AVa & AVe and k-AVa1 & K-AVe2 (p>0,05). Conclusion: There was difference between compressive strength scaffold combinations of chitosan and Aloe vera extracted water and ethanol, and the most highest compressive strength is AVa.